Genetic Susceptibility to Enteroaggregative Escherichia coli Diarrhea: Polymorphism in the Interleukin-8 Promotor Region - Jiang, Zhi-Dong; Okhuysen, Pablo C.; Guo, Dong-Chuan; He, Rumin; King, Terri M.; DuPont, Herbert L.; Milewicz, Dianna M. (The Journal of infectious diseases, 2003)
Enteroaggregative Escherichia coli (EAEC) infection can be identified in 26% of travelers with diarrhea and is associated with fecal interleukin (IL)–8 production. We hypothesized that single-nucleotide polymorphisms (SNPs) in the IL-8 gene are associated with EAEC-related symptoms. Fecal IL-8 production and IL-8 SNPs at 5 loci were identified in 69 US students who remained in Mexico for 5 weeks; 23 subjects had EAEC-associated diarrhea, 7 were asymptomatic EAEC carriers, 22 had nonspecific diarrhea, and 17 were asymptomatic without an enteropathogen. The chances of having EAEC-associated diarrhea were significantly increased among those with the AA genotype at the −251 position (odds ratio [OR], 208.51; 95% confidence interval [CI], 28.5–1525.36) and among those with AT genotype (OR, 14.3; 95% CI, 1.98–105.74), compared with those with the TT genotype at the −251 position. Among subjects with EAEC-associated diarrhea, the AA genotype at the −251 position produced greater concentrations of fecal IL-8 than those with the AT or TT genotype (P=.0053). In the present study, the AA genotype at the −251 position was associated with the occurrence of EAEC-associated diarrhea and increased levels of fecal IL-8